Assessment of Heterosis for Root Yield and Attributing Traits in Ashwagandha [Withania somnifera (L.) Dunal] - Balakrishnan, Adithya P; Patel, N. B.; Patel, M. P. (International Journal of Bio-resource and Stress Management, 2022)
A study was conducted was conducted to estimate the extent of heterosis for root yield and attributing traits in ashwagandha at the Botanical Garden, Department of Genetics and Plant Breeding, C. P. C. A, S. D. Agricultural University, Sardarkrushinagar, Gujarat, India. Thirty six hybrids were generated from the diallel mating design of 9 diverse parents during October 2018 – March 2019 (rabi season). Fourty five entries were evaluated in RBD with 3 replications during October 2019–March 2020 (rabi season) for the yield and attribuiting traits. The root traits are given more emphasis because of its economic value.All the forty-five genotypes exhibited moderate to good mean performance along with an adequate amount of variability among and between the parents and hybrids. Most of the hybrids showed highly significant better parent and standard heterosis in desirable direction for the traits considered. The hybrids like SKA 10×JA 20, JA 134×AWS 1, SKA 24×SKA 26, SKA 24×AWS 1, SKA 11×AWS 1, SKA 11×SKA 26 and JA 20×AWS 1 were with a markedly significant heterotic response for fresh root yield trait. The results also suggest that the cross JA 134×AWS 1is appropriate to exploit heterosis in root length, fresh root yield and dry root yield. Further evaluation and generation advancement of these successful crosses can derive transgressive segregants and hybrids with high yield potential for commercialization.